Establishment and characterization of new tumor xenografts and cancer cell lines from EBV-positive nasopharyngeal carcinoma. Issue 1 (December 2018) - Lin, Weitao; Yip, Yim; Jia, Lin; Deng, Wen; Zheng, Hong; Dai, Wei; Ko, Josephine; Lo, Kwok; Chung, Grace; Yip, Kevin; Lee, Sau-Dan; Kwan, Johnny; et al.
Abstract The lack of representative nasopharyngeal carcinoma (NPC) models has seriously hampered research on EBV carcinogenesis and preclinical studies in NPC. Here we report the successful growth of five NPC patient-derived xenografts (PDXs) from fifty-eight attempts of transplantation of NPC specimens into NOD/SCID mice. The take rates for primary and recurrent NPC are 4.9% and 17.6%, respectively. Successful establishment of a new EBV-positive NPC cell line, NPC43, is achieved directly from patient NPC tissues by including Rho-associated coiled-coil containing kinases inhibitor (Y-27632) in culture medium. Spontaneous lytic reactivation of EBV can be observed in NPC43 upon withdrawal of Y-27632. Whole-exome sequencing (WES) reveals a close similarity in mutational profiles of these NPC PDXs with their corresponding patient NPC. Whole-genome sequencing (WGS) further delineates the genomic landscape and sequences of EBV genomes in these newly established NPC models, which supports their potential use in future studies of NPC. The lack of appropriate models restricts pre-clinical research for nasopharyngeal carcinoma (NPC). Here the authors report the development and characterization of NPC patient-derived xenografts (PDXs), and EBV positive NPC cell line from patient tumor, and suggest their potential use in future NPC research.